Digital Intra-Party Democracy: An Exploratory Analysis of Podemos and the Labour Party. Issue 1 (21st June 2021) - García Lupato, Fabio; Meloni, Marco
Abstract: The role of technology is growing in intra-party democracy (IPD) processes. This article presents a proposal for analysing digital IPD, by applying empirical democratic theory dimensions. To test our methodology, we analyse two different types of parties, a new digital one, Pos, and a traditional one undergoing reform, the Labour Party. Our analysis shows, first, that the application of technology is not neutral, with a differential impact depending on the specific democratic dimension considered and, secondly, that—due to convergent developments—new and established parties are closer in their digital IPD than expected. These results point out the relevance, for the ongoing debate on the quality of IPD, of considering the impact of digital on different democratic dimensions and its evolution over time.